An investigation into the body temperature, respiration rate, pulse rate and skin temperature of dairy cows under New Zealand conditions, and a review of existing knowledge on animal climatology with particular reference to cattle : thesis submitted in part fulfilment of the degree M. Agric. Sci. - Patchell, Murray Rex (Massey University, 1951)
Domestication of animals had only to begin before it became evident to man that some shelter from heat, cold and other environmental extremes was desirable for the animals as well as himself. Down through the ages end particularly in the present century refinement of methods, materials and degree of shelter have been added. There has not been a refinement corresponding in knowledge of the environmental influence in the range between obviously harmful extremes. Narrow margins for farm profit, increasing attention to production efficiency, increasing cost of shelter, war and post-war demands for high production, have exerted increasing pressure to correct this situation. The delay in attempting to get more accurate information on objectives in environmental control has been due to the immensity of the undertaking. Consider the range of environmental variables involved. The environment to be considered includes an almost.infinite variety of combinations of temperature, radiation, humidity, air control, air movement, light, sound space, surfaces, forms, pressure, presence of other animals. and time phases. The range of possible temperatures is vast. Man and animals. occupy a relatively narrow zone. True, they are exposed to the heat of the tropics and the cold of the arctic regions but animals really live, not in the air, but inside their own skins. The active cells of the body are all beneath the skin, the most important of them a long way below the surface. In the process of evolution mammals have arrived at a certain optimal temperature for the body cells and the organism strives to preserve this temperature as closely as possible. The problem is to define the limits of this zone, to describe the mechanism by which the optimal temperature is maintained, and to give an idea of the results when temperature control fails.
Keywords: Environmental control; Cattle body temperature; Cattle physiology